2016
DOI: 10.1002/wsb.706
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of surgical sterilization for managing overabundant suburban white‐tailed deer

Abstract: Based on decades of increasing deer effects on local biodiversity, agricultural damage, and deer-vehicle collisions, we implemented a suburban white-tailed deer (Odocoileus virginianus) research and management program in 2007 on Cornell University lands in Tompkins County, New York, USA. We attempted to reduce deer numbers by surgically sterilizing female deer in the 445-ha suburban core campus via tubal ligation and ovariectomy. From 2007 to 2013, we sterilized 93 deer and radiocollared 67 adult females to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Despite hundreds of deer taken by hunters on Cornell lands and doe sterilization rates of >90%, our camera surveys indicated that by 2012, five years into the program, we had not achieved any reduction in the core deer population (Boulanger & Curtis, ). In response to our failure to reduce the deer population, we eliminated sterilization efforts and established a larger core management area (CMA, approx.…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…Despite hundreds of deer taken by hunters on Cornell lands and doe sterilization rates of >90%, our camera surveys indicated that by 2012, five years into the program, we had not achieved any reduction in the core deer population (Boulanger & Curtis, ). In response to our failure to reduce the deer population, we eliminated sterilization efforts and established a larger core management area (CMA, approx.…”
Section: Methodsmentioning
confidence: 83%
“…Animal rights and animal welfare organizations have long claimed that deer are not responsible for lack of forest regeneration and that there are more humane methods for managing populations (HSUS, , ; PETA, ). However, there is no evidence to date that can support claims that fertility control alone can sufficiently reduce deer abundance in free‐ranging populations (Hobbs & Hinds, ; Raiho, Hooten, Bates, & Hobbs, ; Ransom, Powers, Hobbs, & Baker, ), including our own (Boulanger & Curtis, ). Examples cited as success stories show reduced fertility on islands or in fenced populations (Naugle, Rutberg, Underwood, Turner, & Liu, ; Rutberg, Naugle, Thiele, & Liu, ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Surgical sterilization is an irreversible way of controlling fertility, requiring veterinary involvement. Evidence of efficacy of this method in population reduction is not conclusive; other deer may move in from outside, and sterilization is expensive and difficult to use on a larger scale (Boulanger & Curtis, ). While acknowledging that research on effectiveness of surgical sterilization is ongoing, we will not consider this option further.…”
Section: Introductionmentioning
confidence: 99%